Use of the pCONus as an adjunct to coil embolization of acutely ruptured aneurysms. (13th July 2016) - Pérez, M Aguilar; Bhogal, P; Moreno, R Martinez; Wendl, C; Bäzner, H; Ganslandt, O; Henkes, H
Abstract : Introduction: Coil embolization of ruptured aneurysms has become the standard treatment in many situations. However, certain aneurysm morphologies pose technical difficulties and may require the use of adjunctive devices. Objective: To present our experience with the pCONus, a new neck bridging device, as an adjunct to coil embolization for acutely ruptured aneurysms and discuss the technical success, angiographic and clinical outcomes. Methods: We conducted a retrospective review of our database of prospectively collected data to identify all patients who presented with acute subarachnoid hemorrhage that required adjunctive treatment with the pCONus in the acute stage. We searched the database between April 2011 and April 2016. Results: 21 patients were identified (13 male, 8 female) with an average age of 54.6 years (range 31–73). 8 aneurysms were located at the basilar artery tip, 7 at the anterior communicating artery, 4 at the middle cerebral artery bifurcation, 1 pericallosal, and 1 basilar fenestration. 61.8% patients achieved modified Raymond–Roy classification I or II at immediate angiography, with 75% of patients having completely occluded aneurysms or stable appearance at initial follow-up. There were no repeat aneurysmal ruptures and two device-related complications (no permanent morbidity). Four patients in our cohort died. Conclusions: Use of the pCONus is safe and effective in patients with acutely ruptured aneurysms and carries a high rate of technical success.